Effectiveness of Patent License Arrangements in Encouraging Technology Transfer in Indonesia - Thalib, Nur Aisyah; Thalib, Abd (Pandecta Research Law Journal, 2025)
Patent licensing is an important instrument in promoting technology transfer, especially in developing countries like Indonesia. However, the implementation of patent licensing still faces various challenges, both from the regulatory side and in practice on the ground.This study aims to evaluate the effectiveness of patent licensing legal regulations based on Law Number 13 of 2016, as well as to identify structural and institutional barriers in its implementation. Using a normative legal approach complemented by empirical literature studies, this research found that the lack of detailed regulations regarding the substance of licenses and the weak government oversight are the main obstacles. Derivative regulations and the strengthening of reporting and evaluation mechanisms are needed so that patent licenses truly function as a means of sustainable and fair technology transfer.